Use of new technologies in the teaching of methodology and practice of scientific research: a report of experience - França, Andressa Silvério Terra (Revista Hipótese, 2019)
The present work addresses an educational experience mediated by the use of new technologies in higher education. The development of ICTs in the contemporary world, especially on the Internet, bringing in its curriculum a series of changes in society, including education here. Not only is a student-teacher exchange happening to be rethought, but also new forms of teaching and learning acquire a new format, more dynamic and interactive, an end to accompany as ongoing transformations. On the other hand, what is happening is difficult and difficult terrain to be answered, especially in the initial cycles. With this in mind, this paper aimed to show the importance of the use of social networks and audiovisual resources, based on an account of a practice developed with the students of Fatec Itapetininga / SP.